Characterizing and sourcing ambient PM2.5 over key emission regions in China II: Organic molecular markers and CMB modeling. (August 2017) - Zhou, Jiabin; Xiong, Ying; Xing, Zhenyu; Deng, Junjun; Du, Ke
Abstract: From November 2012 to July 2013, a sampling campaign was completed for comprehensive characterization of PM2.5 over four key emission regions in China: Beijing-Tianjin-Hebei (BTH), Yangzi River Delta (YRD), Pearl River Delta (PRD), and Sichuan Basin (SB). A multi-method approach, adopting different analytical and receptor modeling methods, was employed to determine the relative abundances of region-specific air pollution constituents and contributions of emission sources. This paper is focused on organic molecular marker based source apportionment using chemical mass balance (CMB) receptor modeling. Analyses of the organic molecular markers revealed that vehicle emission, coal combustion, biomass burning, meat cooking and natural gas combustion were the major contributors to organic carbon (OC) in PM2.5 . The vehicle emission dominated the sources contributing to OC in spring at four sampling sites. During wintertime, the coal combustion had highest contribution to OC at BTH site, while the major source contributing to OC at YRD and PRD sites was vehicle emission. In addition, the relative contributions of different emission sources to PM2.5 mass at a specific location site and in a specific season revealed seasonal and spatial variations across all four sampling locations. The largest contributor to PM2.5 mass was secondary sulfate (14–17%) in winter at the four sites. The vehicle emission was found to be the major source (14–21%) for PM2.5 mass at PRD site. The secondary ammonium has minor variation (4–5%) across the sites, confirming the influences of regional emission sources on these sites. The distinct patterns of seasonal and spatial variations of source apportionment observed in this study were consistent with the findings in our previous paper based upon water-soluble ions and carbonaceous fractions. This makes it essential for the local government to make season- and region-specific mitigation strategies for abating PM2.5 pollution in China. Highlights: Molecular marker-CMB model was applied to estimate primary contributors to PM2.5 OC. Main contributors to PM2.5 were sulfate, vehicle emission, nitrate, coal combustion. Vehicle emission had the largest impact on PM2.5 mass in PRD region. PM2.5 level was affected by local emissions and regional enriched sources across the sites.